2009
DOI: 10.1128/mcb.00971-08
|View full text |Cite
|
Sign up to set email alerts
|

The Ku80 Carboxy Terminus Stimulates Joining and Artemis-Mediated Processing of DNA Ends

Abstract: Repair of DNA double-strand breaks (DSBs) is predominantly mediated by nonhomologous end joining (NHEJ) in mammalian cells. NHEJ requires binding of the Ku70-Ku80 heterodimer (Ku70/80) to the DNA ends and subsequent recruitment of the DNA-dependent protein kinase catalytic subunit (DNA-PK CS ) and the XRCC4/ligase IV complex. Activation of the DNA-PK CS serine/threonine kinase requires an interaction with Ku70/80 and is essential for NHEJ-mediated DSB repair. In contrast to previous models, we found that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 39 publications
(52 reference statements)
3
55
1
Order By: Relevance
“…The C-terminal Region of Ku80 Is Not Required for Interactions with APLF-Although Ku80 is highly homologous to Ku70, the C-terminal region of Ku80 is divergent and has been shown to be required for cellular radioresistance (30). This region of Ku80 is also required for DNA-PKcs autophosphorylation and activation of Artemis end processing (30).…”
Section: Disruption Of the Aplf-ku Interaction Is Associated With Altmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-terminal Region of Ku80 Is Not Required for Interactions with APLF-Although Ku80 is highly homologous to Ku70, the C-terminal region of Ku80 is divergent and has been shown to be required for cellular radioresistance (30). This region of Ku80 is also required for DNA-PKcs autophosphorylation and activation of Artemis end processing (30).…”
Section: Disruption Of the Aplf-ku Interaction Is Associated With Altmentioning
confidence: 99%
“…This region of Ku80 is also required for DNA-PKcs autophosphorylation and activation of Artemis end processing (30). Therefore, we questioned whether this C-terminal portion of Ku80 might be important for directing interactions with APLF.…”
Section: Disruption Of the Aplf-ku Interaction Is Associated With Altmentioning
confidence: 99%
“…38,39 Furthermore, Ku80 has been shown to stimulate joining and Artemismediated processing of DNA ends. 40 The most widely investigated system of NHEJ is V(D)J recombination that is responsible for antibody diversity and normal immune development (reviewed in ref. 41 and 42).…”
Section: Dna-pk Structure and Its Role In Non-homologous End Joining mentioning
confidence: 99%
“…Similar to this, further studies with DNA-PKcs and Ku80 have shown that the Ku80 C-terminal motif is not essential for DNA-PKcs kinase activity or its ability to localize to DSBs. 38 However, deletion of the C-terminal portion of Ku80 results in radiosensitivity, which is probably due to its importance for phosphorylation of DNA-PKcs at the 2609 cluster and the DNA end processing by the Artemis endonuclease and ultimately end-joining. These data suggest that ATM and DNA-PKcs are both recruited to DSBs via multimeric complexes, but further detailed studies need to be performed to delineate the specific domains/residues required for localization of ATM and DNA-PKcs to DSBs.…”
Section: Recruitment To Dna Double Strand Breaksmentioning
confidence: 99%